The prevalence, penetrance, and expressivity of etiologic IRF6 variants in orofacial clefts patients from sub‐Saharan Africa. Issue 2 (12th January 2017) - Gowans, Lord Jephthah Joojo; Busch, Tamara D.; Mossey, Peter A.; Eshete, Mekonen A.; Adeyemo, Wasiu L.; Aregbesola, Babatunde; Donkor, Peter; Arthur, Fareed K. N.; Agbenorku, Pius; Olutayo, James; Twumasi, Peter; Braimah, Rahman; et al.
Abstract: Background: Orofacial clefts are congenital malformations of the orofacial region, with a global incidence of one per 700 live births. Interferon Regulatory Factor 6 ( IRF6 ) (OMIM:607199) gene has been associated with the etiology of both syndromic and nonsyndromic orofacial clefts. The aim of this study was to show evidence of potentially pathogenic variants in IRF6 in orofacial clefts cohorts from Africa. Methods: We carried out Sanger Sequencing on DNA from 184 patients with nonsyndromic orofacial clefts and 80 individuals with multiple congenital anomalies that presented with orofacial clefts. We sequenced all the nine exons of IRF6 as well as the 5′ and 3′ untranslated regions. In our analyses pipeline, we used various bioinformatics tools to detect and describe the potentially etiologic variants. Results: We observed that potentially etiologic exonic and splice site variants were nonrandomly distributed among the nine exons of IRF6, with 92% of these variants occurring in exons 4 and 7. Novel variants were also observed in both nonsyndromic orofacial clefts (p.Glu69Lys, p.Asn185Thr, c.175‐2A>C and c.1060+26C>T) and multiple congenital anomalies (p.Gly65Val, p.Lys320Asn and c.379+1G>T) patients. Our data also show evidence of compound heterozygotes that may modify phenotypes that emanate from IRF6 variants. Conclusions: This study demonstrates that exons 4 and 7 of IRF6 are mutational 'hotspots' in our cohort and that IRF6 mutants‐induced orofacial clefts may be prevalent in the Africa population, however, with variable penetrance and expressivity. These observations are relevant for detection of high‐risk families as well as genetic counseling. In conclusion, we have shown that there may be a need to combine both molecular and clinical evidence in the grouping of orofacial clefts into syndromic and nonsyndromic forms. Abstract : This is a study on orofacial clefts from three African populations. We have shown evidence of pathogenic variants in our cohort.